ANALISIS GAYA BAHASA DAN MANFAAT DALAM PENDIDIKAN PADA NOVEL WINTER IN TOKYO KARYA ILLANA TAN - I Nyoman Artika Adhikara; A.A. Rai Laksmi; Ni Wayan Eminda Sari (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2022)
Literature is the result of human creative thinking in the form of ideas, thoughts, understandings from the creators which encompass about existences by using imaginative, furthermore literature can also be used as an entertainment for their connoisseur. In this study, the research problem is how is the use of language style and what are the benefits in education which contained in the novel